2018
DOI: 10.21873/invivo.11342
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Microbubble Delivery Targeting Intraplaque Neovascularization Inhibits Atherosclerotic Plaque in an APOE-deficient Mouse Model

Abstract: UTMD targeting intraplaque neovascularization was found to inhibit atherosclerotic plaque in a mouse model of atherosclerosis, suggesting the potential of microbubble-mediated ultrasound technology in aiding drug delivery for atherosclerosis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In conclusion, this is the first demonstration of antiinflammatory efficacy of targeted microbubbles on an earlystage AS model in vitro. In combination with our previous in vivo experiment (6), we believe that UTMD therapy has clinical potential for AS treatment.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In conclusion, this is the first demonstration of antiinflammatory efficacy of targeted microbubbles on an earlystage AS model in vitro. In combination with our previous in vivo experiment (6), we believe that UTMD therapy has clinical potential for AS treatment.…”
Section: Discussionsupporting
confidence: 70%
“…We previously reported that treatment with UTMD targeting Endostar and ICAM-1 inhibited atherosclerotic plaques in animal models (6). Endostar is a modified version of recombinant human endostatin, which is a strong inhibitor of angiogenesis (22) and plaque neovascularization (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiovascular drug delivery, cavitation nuclei are co-administered or loaded with different therapeutics for the treatment of various diseases. For atherosclerosis treatment in an ApoE-deficient mouse model, intercellular adhesion molecule-1-targeted microbubbles carrying the angiogenesis inhibitor Endostar were used (Yuan et al 2018). Upon intermittent insonification over the abdominal and thoracic cavity with 1 MHz ultrasound (2 W/cm 2 intensity, 50% duty cycle) for 30 s with two repeats and another treatment 48 h later, plaque area and intraplaque neovascularization were significantly reduced 2 wk after treatment.…”
Section: Cardiovascular Drug Delivery and Therapymentioning
confidence: 99%
“…The development of novel techniques to enhance the susceptibility of biological systems to acoustic effects has expanded the versatility of ultrasound across both diagnostic and therapeutic domains. In particular, advances in microbubble chemistry have enabled the use of acoustically-responsive droplets as vehicles for the delivery of drugs, including recombinant proteins [ 135 ], small molecules [ 136 ], and genetic material [ 137 ]. In these systems, which vary among applications in their composition and preparation, a therapeutic payload is suspended in a cavitation-sensitive material, often gas or perfluorocarbons, and encapsulated within a stabilizing shell [ 138 ].…”
Section: Acoustic Manipulation Of Ecm-based Scaffoldsmentioning
confidence: 99%